Synthesis of integrated solar thermal networks for domestic and industrial utilization - Abikoye, Semilore Ben Olaoluwa (Department of Chemical Engineering, 2022)
This study involves the development of generic multi-period Mixed Integer Non-Linear Programming (MINLP) based design and optimization methods for integrating solar thermal with domestic and industrial heat networks over multiple time frames based on discrete time intervals/periods. The study also presents a new simultaneous multi-period modelling and design framework for increasing thermal output of an integrated solar thermal-heat pump system. Detailed MINLP superstructure based design and optimization technique is used for the proposed designs while the synthesis of the heat networks was implemented and solved simultaneously in General Algebraic Modelling Systems (GAMS) using SBB solver. The first aspect of the thesis deals with the development of design and optimization model for direct and indirect integration of feasibly attainable solar thermal with industrial heat network. In the model, periodic changes in demand and supply sides of the industrial heat network superstructure, including periodic changes in the amount of heat stored in thermal storage tank, are accounted for using discretized time periods. The developed model was then applied to three kinds of integration scenario for industrial heating which includes pre-heating of single cold stream, targeting of a definite cold stream among multiple industrial cold streams, and pre-heating of multiple cold streams within the heat network. The second part of the study introduces the developed design and optimization model for integrating solar thermal with the heat network of residential buildings. The residential heat network includes water and space heating, periodic heat storage and backup utility, while other essential attributes of the design are incorporated and accounted for periodically in the proposed model. The case study considered involves solar thermal integration with heat supply network of a cluster of buildings considering heat storage and the varying heat requirement profiles of each building in the network. In the case study, two heat storage design alternatives incorporating combined water and space heating networks for three different types of building designs in Slovenia were investigated for the proposed residential integration of solar thermal network. The third aspect of the study presents a multi-period mathematical programming approach for simultaneous design and optimization of a solar thermal source multi-stage heat pump cycle for low/medium temperature heat production. The proposed model accounts for the intermittent changes in solar irradiation and ambient temperatures, as well as their effects on heat output from the system, while the dynamic operating conditions and thermodynamic features of the integrated system are also accounted for according to diverse ambient temperatures. The conceptual framework for the combined solar thermal-heat pump design rests on the idea that the thermal output of solar heat network designs, such as those described in the first two parts of the thesis, could be further enhanced by incorporating heat pump technology with the solar thermal network. The results obtained from the studies indicate good prospect for solar thermal integration with domestic and industrial heat networks; it also offers opportunities for enhanced solar heat output through systematic combination of solar thermal with heat pump cycle. For the case of industrial cold stream pre-heating, the results obtained show that the average attainable solar heat increases (i.e. by 80.9 W/m2 ) up to collector area of about 6,500 m2 , beyond which the average solar heat attainable increase dropped to 16.7 W per additional m2 of collector area up to 10,000 m2 . However, for the selected case study of a dairy plant, an average solar heat output of about 75 W/m2 of collector is obtained with linear increase in the average attainable heat load up to certain collector area (on case- by-case basis), after which it is observed that further increase in collector area does not result in much increase in the obtained heat load. For the first design alternative in the integrated residential solar thermal with heat storage network study, the results show that about 7.4 % of the total heat required by the buildings (for water and space heating) in winter months could be satisfied by solar thermal while the total heat demand for water heating in summer months could be fully satisfied by solar. Whereas the result obtained from the second design with a single heat storage tank shows that for collector area of about 18.8 m2 , only 25% of the energy required in the buildings could be satisfied by solar while for a collector area of 601.2 m2 , up to 92% of heat demand could be satisfied by solar. The results for the integrated solar thermal and heat pump systems show relative operational stability in the heat output regardless of season with 4,904.9 kW and 4,714.8 kW of heat harvested from the system in March and August respectively at an average coefficient of performance of 1.68. The models developed in this thesis are generic in that the model equations are formulated independent of the data. Hence, they can be applied to any integrated solar heating network in any location with known geographical coordinates and meteorological information.